Analisis Kadar Prothrombin Time (PT) Pada Pasien Diabetes Mellitus Tipe 2 - Nurhilaliyah Nurhilaliyah; Dewi Susandra; A. Meryam Susanti (Pelantar Press, 2025)
Prothrombin Time (PT) levels are an important parameter in laboratory tests used to measure blood clotting time through the extrinsic pathway and the common pathway. In patients with Type 2 Diabetes Mellitus, metabolic disorders can affect the coagulation system and increase the risk of bleeding or thrombosis. This study aims to determine the relationship between blood sugar levels and Prothrombin Time levels in patients with Type 2 Diabetes Mellitus. This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 30 Type 2 Diabetes Mellitus patients undergoing outpatient or inpatient care at Labuang Baji General Hospital in Makassar. Data collection was conducted through blood sampling by medical staff, followed by blood glucose and Prothrombin Time measurements in the laboratory. Data analysis utilized Pearson's correlation test. The results showed that most patients had PT levels within the normal range despite high blood sugar levels. However, some patients experienced a significant increase in PT levels, which may indicate coagulation disorders. Statistical tests revealed a weak and statistically insignificant association between blood sugar levels and PT. The conclusion of this study is that blood sugar levels are not significantly associated with Prothrombin Time levels in patients with Type 2 Diabetes Mellitus